Endovascular Neurosurgery in the Netherlands: Historical Developments and Achievements - de Vries, Joost; Willems, Peter; Boogaarts, Hieronymus; Grotenhuis, André (Frontiers in Surgery, 2018)
The historical developments of endovascular neurosurgery in the Netherlands are described.